2002
DOI: 10.1074/jbc.c100609200
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Modification of tRNAs

Abstract: The product of the miaB gene, MiaB, from Escherichia coli participates in the methylthiolation of the adenosine 37 residue during modification of tRNAs that read codons beginning with uridine. A His-tagged version of MiaB has been overproduced and purified to homogeneity. Gel electrophoresis and size exclusion chromatography revealed that MiaB protein is a monomer. As isolated MiaB contains both iron and sulfide and an apoprotein form can chelate as much as 2.5-3 iron and 3-3.5 sulfur atoms per polypeptide cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…Formation of ms 2 i 6 A, which consists in the introduction of a methylthio group at position 2 of adenosine, is one of those rare examples. The MiaB protein, which participates to this reaction is, accordingly, a redox protein and the first and so far unique tRNA-modifying enzyme containing an iron-sulfur cluster required for activity (17,18). The cluster is a [4Fe-4S] The reaction mixture (300 l) incubated at 37°C contained 1 mg of i 6 A-37-tRNAs, mixA, 70 M MiaBTm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation of ms 2 i 6 A, which consists in the introduction of a methylthio group at position 2 of adenosine, is one of those rare examples. The MiaB protein, which participates to this reaction is, accordingly, a redox protein and the first and so far unique tRNA-modifying enzyme containing an iron-sulfur cluster required for activity (17,18). The cluster is a [4Fe-4S] The reaction mixture (300 l) incubated at 37°C contained 1 mg of i 6 A-37-tRNAs, mixA, 70 M MiaBTm.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of BioB enzyme, which also catalyzes C-H to C-S bond conversion reactions, this motif was shown to provide cysteine ligands for a catalytically essential [4Fe-4S] 2ϩ/1ϩ cluster (16). Such a cluster is present also in MiaB protein (17,18), and it is thus very likely that MiaB and BioB employ similar radical mechanisms for activation of sulfur and its insertion into their respective substrates.Recently, we cloned, expressed, and characterized by bio-* The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this feature suggested that translation would be allowed only from the second AUG, we made two constructs to verify whether only a 29,057-Da protein is overexpressed (if the second AUG is used) or a 31,140-Da protein is also overexpressed (if the first AUG is used). The two possible ORFs for the miaE gene were amplified from the genomic DNA of S. typhimurium by PCR and cloned into a pT 7 -7 vector as previously described (7,9). The resulting plasmids are named pT 7 -miaE1 for the first AUG start codon and pT 7 -miaE2 for the second AUG start codon.…”
Section: Cloning Expression and Purification Of Miae From S Typhimmentioning
confidence: 99%
“…In particular, redox modifications of tRNAs have been surprisingly scarcely studied as compared with nonredox reactions such as methylations for example. Recently, we discovered and characterized the first, and so far the only, ironsulfur enzyme involved in tRNA modification (7)(8)(9). This enzyme, the product of the miaB gene (Scheme 1), catalyzes a difficult C-H to C-S bond conversion during the thiomethylation of i 6 A-37 (N-6-isopentenyl adenosine) to ms 2 i 6 A-37 (2-methylthio-N-6-isopentenyl adenosine).…”
mentioning
confidence: 99%